Use of chemically modified azoles for use in copper corrosion inhibitors in acid medium: theoretical and experimental aspects - Costa, Stefane Nunes (2023)
This work presents the application of modified azole molecules (imidazole and triazole) for application as a corrosion inhibitor for copper electrode in sulfuric acid 0.5 mol L-1. The compounds to be evaluated are: 4-(1H-imidazole-1-yl)benzaldehyde (IB), 4-(1H-imidazole-1-yl)aniline (IA), [4-(1H-imidazole-1-yl)-Phenyl]Methanol (IFM), 4-(Imidazole-1-yl)-Phenol (IF), 1-phenyl-2-(1H-1,2,4-triazole-1-yl)ethanone (TR-1), 1-(2,4-difluorophenyl)-2(1H-1,2,4-triazole-1-yl)ethanone (TR-2), 1-(4-chlorophenyl)-2-(1H-1, 2, 4-triazole-1-yl)ethanone (TR-3) and 1-(p-toluyl)-2-(1H-1,2,4-triazole-1-yl)ethanone (TR-4). Electrochemical techniques such as Open Circuit Potential (OCP), Linear Potentiodynamic Polarization (LPP) and Electrochemical Impedance Spectroscopy (EIS) were performed, as well as chemical modeling was applied using Monte Carlo and DFT techniques. All imidazole derivatives inhibited copper corrosion, and the inhibition values were between 80 and 94%. A good correlation between the values of inhibition efficiency and Gibbs adsorption energy were found, showing that the more negative Gibbs energy, the better interaction of the corrosion inhibitor with the copper surface, decreasing its corrosion in 0.5 mol L-1 medium H2SO4. DFT calculations showed differences in the electronic and reactivity properties of imidazole and other molecules. The higher corrosion inhibition of imidazole derivatives can be explained by the electrophilic characteristic of these molecules, since there are empty molecular orbitals scattered mainly in benzene rings that transfer metal-to-binder charge, receiving electron density from the copper surface. By backbonding, according to the Fukui electronic functions and the potential charge distribution considering the electrostatic potential map. Regarding the triazoles, the analysis of the electrochemical data showed that TR-2 presented the highest inhibition efficiency (95.12% for LPP and 83.55% for EIE). The isothermal analysis showed that TR-s presented the highest adsorption constant, as well as the lowest Gibbs adsorption energy. Considering the Monte Carlo simulations, the TR-2 molecule is adsorbed on the electrode surface by the triazole group, which favors the creation of a stable film on the electrode. Electronic analysis of the DFT calculations shows that the polarity and LUMO energies of the molecules play an important role in creating a coordination complex between the electrode surface and the TR-2 inhibitor molecule. Keywords: corrosion inhibitors, imidazole, triazole, copper, DFT